Effect of thawing temperature on motion characteristics of frozen-thawed ram spermatozoa - BAG, SADHAN; JOSHI, ANIL; MATHUR, A K; RAWAT, P S; MITTAL, J P (The Indian Journal of Animal Sciences, 2012)
Semen of adult Malpura rams was processed for freezing after initial dilution @ 1000 million spermatozoa/ml. Extended semen samples were aspirated into 0.5 ml straws and frozen in a programmable cell freezer. Straws were thawed at 50°C or 60°C for 10 sec and the motion characteristic of spermatozoa were assessed by computer-assisted sperm analysis technique. The mean post·thaw recovery of motile spermatozoa at 60°C thawing was significantly higher (P<0.01) ranging from 72.1 to 72.9 % in 2 replicates as compared to 53.8 to 55.4 % at 50°C thawing. The effect of replication was significant (P<0.01) only for beat frequency of spermatozoa. The results indicate that thawing at 60°C has also a significant effect on % rapid. %linearity, % curvilinear velocity, average path velocity, straight line velocity (P<0.01) and beat frequency of spermatozoa (P<0.05) as compared to thawing at 50°C. However, there was no significant effect of thawing temperature on % medium, % slow, % straightness and amplitude of lateral head displacement of spermatozoa.